If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2z + -28 = 8 + 8z Reorder the terms: -28 + 2z = 8 + 8z Solving -28 + 2z = 8 + 8z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-8z' to each side of the equation. -28 + 2z + -8z = 8 + 8z + -8z Combine like terms: 2z + -8z = -6z -28 + -6z = 8 + 8z + -8z Combine like terms: 8z + -8z = 0 -28 + -6z = 8 + 0 -28 + -6z = 8 Add '28' to each side of the equation. -28 + 28 + -6z = 8 + 28 Combine like terms: -28 + 28 = 0 0 + -6z = 8 + 28 -6z = 8 + 28 Combine like terms: 8 + 28 = 36 -6z = 36 Divide each side by '-6'. z = -6 Simplifying z = -6
| .07*x=84 | | 5x-12=-17 | | 11/3*-7/2*4/5-x | | 3(a-1)=-17 | | 2*x^3-2*x^2-36*x+5=0 | | 0=121p^2-100 | | m*(-4/5)=2,23 | | 4(3x+4x)-1=91 | | .5z-1=-13 | | 7-2Inx=3 | | 800x-0.55=400x+0.45 | | f(x)=9x^2+4x+9 | | 2(j-4)=10 | | 2*16+46=x | | 2*16+46= | | x^2-cx-6c^2=0 | | 5x^10-8x^7= | | .66c+6=18 | | 3x/5-2 | | 20=y/6 | | 3^2/2n4=3 | | (1-2sinx)/cosx | | 2(5x-8)=7-(5-x) | | 1-2sinx/cosx | | (3x+1)2=8 | | -18=.33x-(-9) | | x^2+676x-11840=0 | | 50/288 | | sin(x)+sin(3x)= | | -4.9t^2+12t+600=0 | | x(6-x)-7.2=0 | | 26+y+26y=80 |